Lifestyle as a Mediator: The Influence of Content Marketing, Brand Equity, and Influencers Marketing on Aerostreet Purchase Decisions - Leif Kaysa F; Suwignyo Widagdo; Muhaimin Dimyati (Trescode Green Organization, 2025)
Lifestyle as a Mediator: The Influence of Content Marketing, Brand Equity, and Influencer Marketing on Aerostreet Purchase Decisions in Three Sub-Districts of Jember City. This study aims to analyze the direct and indirect effects of content marketing, brand equity, and influencer marketing on purchase decisions, with lifestyle as a mediating variable. The research was conducted among Generation Z consumers who use Aerostreet products in Jember City, characterized by digital-based consumption and active lifestyles. This study uses a quantitative method with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Data were collected through questionnaires distributed to respondents who met the criteria. The variables examined include content marketing, brand equity, influencer marketing, lifestyle, and purchase decision. The analysis results indicate that content marketing, brand equity, and influencer marketing have a direct effect on lifestyle. Content marketing and influencer marketing have a direct effect on purchase decisions, while brand equity does not have a direct effect on purchase decisions; however, it does not play a significant role as a mediator between the three independent variables and purchase decisions. These findings emphasize the importance of developing digital marketing strategies that align with the lifestyle of Generation Z, as well as the need to enhance content authenticity and brand relevance through consistent and personalized approaches.